PENGARUH UPAH DAN PENGAWASAN TERHADAP PRODUKTIVITAS KARYAWAN STUDI KASUS PADA PT. TONGA TIUR PUTRA KRAGAN KABUPATEN REMBANG - Mohammad Kanzunnudin (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2007)
With the purpose ro increase the productivity, all elements that support the productivity have to be concerned; they are wage and supervision. The produktivity improvement being disposed on management maintenance. Management runs its programs while at the same, this tries to carry ona well relation between the employer.The result of this study shows that the variables of wage and supervision, have influence toward the employees’ productivity on PT. Tonga Tiur Putra kragan. The calculation of Anova test using a multiple regreasion, shows that the value for F count as 227.033, and value for F table as 0.9946.For the F count > F table, with the probability level much lower than 0.05, this can be concluded that, together, both wage and supervision have their influences toword the employees’ producity. The SPSS shows the value for R2 as 0.05, and this means that 87,1& of producivity variatioan, might be explained from the variation of both two independent variables; wage and supervision. While the rest (100% 87,1% = 12,9) can be explaint from other causes beyond both two variables. The calculation result as seen from the table shows that SR X1 and SR X2 for wage as 0,62674 and for supervation as 99,37352. These results support that supervision has more influence towardemployees’ productivity.